Precipitation of sodium silicofluoride (Na2SiF6) and cryolite (Na3AlF6) from HF/HCl leach liquors of alumino-silicates - Kumar M.; Babu M.N.; Mankhand T.R.; Pandey B.D. (My University, 2025)
The HF + HCl leach liquor generated from the dissolution of silica, alumina and silicate gangue minerals in a low-grade molybdenite concentrate contains H2SiF6 and H3AlF6. Studies were conducted to recover the two valuable fluorides as Na2SiF6 and Na3AlF6 (synthetic cryolite) by precipitation with Na2CO3 from the leach liquor. An initial investigation was carried out to determine the precipitation conditions for Na 2SiF6 and Na3AlF6 from their individual acid solutions. Subsequently, the conditions were determined for the selective precipitation of the two fluorides from a synthetic mixed acid solution similar to the leach liquor. When the acid solution was neutralized with 3 mol/L Na2CO3, Na2SiF6 precipitated first at pH 1.35 whilst Na3AlF6 required an increase in pH above 2.2 before it precipitated. Maximum recovery of the two fluorides was best achieved at about 50 °C. A similar trend was observed for the precipitation of Na2SiF6 and Na3AlF 6 from the leach liquor of molybdenite upgrading. Phases of precipitated fluorides were identified by XRD and surface morphology by SEM. The purity of the Na2SiF6 precipitate was 99.5% whereas Na3AlF6 was contaminated with Na3FeF 6. © 2010 Elsevier B.V. All rights reserved.